The Recruitment of Academic Staff in Higher Educational Institutions of Azerbaijan - Ibadova, Asmar; Azimova, Fidan; Nazirova, Habiba; Mammadova, Yegana (ADA University, 2021)
The foundation of an educational institution is the academic personnel. The process of recruiting academic staff in higher education institutions (HEIs) is an important step for future development as the chosen candidates provide students of said institutions with education, fulfilling the primary goal of any educational organization. The study analyzes the recruitment process of the academic staff in HEIs in Azerbaijan. The research examined some variables related to the recruitment process and recommended further improvements. A qualitative method and a diagnostic research design were used. The analysis found that different departments and approaches are utilized in universities. However, there are three key requirements of the recruitment process in all universities: universities’ needs, labor code, and the regulations of the Ministry of Education. Additionally, the study revealed that while HR department partakes in the overall recruitment process, in the majority of cases analyzed, they have virtually no say in the final hiring decision as it is made by the committee members, deans, and rectors. Agism and the inability to find right candidates for the position were noted as challenges by the research participants. The study revealed that the main hindrances in the effective recruitment process are the vagueness of the recruitment announcement, the lack of well-developed procedure and cooperation between the departments. Research suggests the recruitment process of academic staff in higher education in the Republic of Azerbaijan to be coordinated between the universities as they can make the search for a good candidate run more smoothly.
Keywords: Education; Recruitment--Education; Academic staff--Azerbaijan; Higher education--Azerbaijan; Education management